The prognostic impact of incidental prostate cancer following radical cystoprostatectomy: a nationwide analysis. (2nd November 2018) - Jønck, Simon; Helgstrand, John Thomas; Røder, Martin Andreas; Klemann, Nina; Toft, Birgitte Grønkaer; Brasso, Klaus
Abstract: Background: To determine the prevalence and prognostic impact of incidental prostate cancer in patients undergoing radical cystoprostatectomy. Methods: A nationwide population-based study of incidental prostate cancer diagnosed following radical cystoprostatectomy. Information on vital status, Gleason score, positive and negative tumor margins, pT-category and subsequent prostate cancer therapies were obtained from the Danish Prostate Cancer Registry and by manual chart review. Results: A total of 1, 450 men who underwent radical cystoprostatectomy in Denmark from 1995–2011 were identified. Forty-six men were excluded from analysis, thus 1, 404 patients were eligible. The median follow-up was 7.8 years. A total of 466 (33.2%) had incidental prostate cancer diagnosed. No statistical differences in 10- and 15-year cumulative overall mortality were observed when comparing men with, or without, incidental prostate cancer. In men diagnosed with incidental prostate cancer, neither Gleason score, positive surgical margins or locally advanced prostate cancer (pT3–4) was associated with mortality. Only 0.9% received post-operative prostate cancer-related treatment. Conclusion: In this population-based cohort of patients with incidental prostate cancer diagnosed at radical cystoprostatectomy, we found no impact of incidental prostate cancer on overall mortality, regardless of Gleason score, surgical margin status and pathological T-category. Patients diagnosed with incidental prostate cancer following radical cystoprostatectomy are unlikely to benefit from additional follow-up.